Satellite and terrestrial radio positioning techniques : a signal processing perspective - Dardari, Davide; Falletti, Emanuela; Luise, Marco (Academic Press/Elsevier, 2012)
* The first book to combine satellite and terrestrial positioning techniques - vital for the understanding and development of new technologies * Written and edited by leading experts in the field, with contributors belonging to the European Commission's FP7 Network of Excellence NEWCOM++ Applications to a wide range of fields, including sensor networks, emergency services, military use, location-based billing, location-based advertising, intelligent transportation, and leisure Location-aware personal devices and location-based services have become ever more prominent in the pa.